Cross-sectional survey on public health informatics workforce in China: issues, developments and the future. Issue 11 (November 2015) - Qi, X.; Wang, Y.; Xia, L.; Meng, Y.; Li, Y.; Yu, S.; Su, X.; Jin, S.; Li, Y.; Ge, H.; Zhang, Y.; Zhuang, D.; et al.
Abstract: Objective: To explore the current situation and issues related to the development of the public health informatics (PHI) workforce in provincial and prefectural centers for disease control and prevention (CDCs) in China, and to describe the corresponding strategies to address these issues for the future. Study design: National cross-sectional study. Methods: One thousand two hundred and eighty-one respondents were selected at random from provincial and prefectural CDCs. The survey used a self-administered, structured questionnaire with an online data collection tool that integrated data quality control and user management. The questionnaire was divided into seven main categories. Score percentage of satisfaction and proportion in each part were calculated. Descriptive statistics were used to analyse the data, stratifying by country region, CDC level, job role and educational level. Results: One hundred and sixty staff from provincial CDCs and 1121 staff from prefectural CDCs were selected. Only 7.4% (33/445) of prefectural CDCs were not involved in this survey, due to lack of PHI practitioners. CDC staff in the eastern region were predominantly aged 30–39 years (39.5%), which was much younger compared with the other regions ( P = 0.0012). Only 34 respondents (2.7%) had academic majors in both health and information technology. More staff had Master's degrees and a higher level of education (18.7%) in the eastern region compared with the other regions ( P < 0.0001). Staff in the eastern region in high-level positions and with a higher level of education were more knowledgeable about PHI strategy. Prefectural CDC staff were more satisfied with their work and training than provincial CDC staff. In the eastern region, 34.9% of staff were hired through competitive recruitment, and 57.8% of staff had received a job description with detailed information about their responsibilities, which was higher than in the other regions. Staff in the western region were more likely to leave if a better job became available (37.7%) compared with staff in the other regions ( P = 0.0116). Conclusion: This study found regional disparities in PHI workforce development, possibly related to disparities in overall regional development. Findings showed a severe shortage of staff with a background in PHI, and occupational development paths were clearly lacking. Based on this study of current workforce issues, a comprehensive strategy for PHI workforce development in China has been described.